The Implementasi Pembelajaran PAI Berbasis Platform Interaktif Dalam Upaya Meningkatkan Kualitas Pembelajaran (Studi Kasus SD Muhammadiyah Pandes): Indonesia - Lalu Wire Sanni Atmaja; Hendro Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic Religious Education (PAI), also known in Muhammadiyah schools as ISMUBA, is one of the important aspects in the character and moral development of elementary school students. However, in practice, ISMUBA learning in many schools still faces challenges in the form of limited methods used, which tend to be monotonous and less engaging for students. This study aims to examine the implementation of ISMUBA learning based on interactive platforms in improving the quality of education at SD Muhammadiyah Pandes Bantul. The method used in this research is a qualitative approach with a case study design. Data collection techniques were carried out through observation, in-depth interviews with teachers and students, as well as the distribution of questionnaires to obtain information related to changes in student motivation and engagement in ISMUBA learning. The collected data were analyzed using the Miles and Huberman analysis technique. The research results show that the implementation of interactive platforms in ISMUBA learning at SD Muhammadiyah Pandes brings various benefits, such as flexible access to materials, increased student motivation, and ease of evaluation. The use of applications like Kahoot, Quizizz, and Google Classroom makes students more engaged thanks to elements of gamification and material personalization. However, the challenges faced include limited devices, unstable internet access, and teachers' readiness to utilize technology. To address these challenges, the school has adopted hybrid learning methods, task flexibility, and technology training for teachers. Support for facilities and the development of technological infrastructure are also priorities to ensure the success of this program. With strong collaboration between schools, teachers, students, and the government, ISMUBA learning based on interactive platforms has great potential to improve the overall quality of education.